2001
DOI: 10.1037/0022-3514.81.6.1119
|View full text |Cite
|
Sign up to set email alerts
|

Rigid and extreme: A geometric representation of personality disorders in five-factor model space.

Abstract: Personality disorder rigidity and extremity can be geometrically defined and operationalized within the 5-factor model (FFM) of personality. A series of geometric and substantive assumptions were derived and then tested in samples of college students (N = 1,323) and psychiatric patients (N = 86). Normal and disordered personalities were found to coexist in a variety of regions of the FFM multivariate space. Within regions, the profiles of normal and disordered personalities were very similar in characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 34 publications
0
45
0
4
Order By: Relevance
“…The same five dimensions (neuroticism, extroversion, openness to experience, agreeableness and conscientiousness) are assumed to underlie both normal and abnormal personality characteristics (Digman, 1990;John & Srivastava, 1999;McCrae & John, 1992;Wiggins, 1996). Abnormal personalities are viewed as maladaptively extreme variants of the five basic factors of personality, and personality disorders can be understood in terms of their relative position on the five primary dimensions O'Connor & Dyce, 2001;Widiger, 1993Widiger, , 2000Widiger, Trull, Clarkin, Sanderson, & Costa, 1994).…”
Section: The Dimensional Structure Of Personality Disordersmentioning
confidence: 99%
“…The same five dimensions (neuroticism, extroversion, openness to experience, agreeableness and conscientiousness) are assumed to underlie both normal and abnormal personality characteristics (Digman, 1990;John & Srivastava, 1999;McCrae & John, 1992;Wiggins, 1996). Abnormal personalities are viewed as maladaptively extreme variants of the five basic factors of personality, and personality disorders can be understood in terms of their relative position on the five primary dimensions O'Connor & Dyce, 2001;Widiger, 1993Widiger, , 2000Widiger, Trull, Clarkin, Sanderson, & Costa, 1994).…”
Section: The Dimensional Structure Of Personality Disordersmentioning
confidence: 99%
“…Several studies have attempted to locate abnormal personality traits within the FFM factor space (see O'Connor & Dyce, 2001). While the FFM has been shown to exhibit correlations with Axis II clinical constructs (e.g., Widiger et al, 2002), in practice, such correlations are typically observed even between quite unrelated psychometric measures, and are of little psychological importance, being attributable largely to overlapping media of measurement variance (e.g., intercorrelations between unrelated self-report scales)..…”
Section: The Ffm and Abnormal Personality Structurementioning
confidence: 99%
“…A variety of studies have indicated, for example, that personality structure is essentially the same in clinical and nonclinical samples (O'Connor, 2002), that normal and abnormal personality are strongly related at the etiologic level (Jang & Livesley, 1999;Markon, Krueger, Bouchard, & Gottesman, 2002), and that abnormal personality can be modeled as extremes of normal personality variation (O'Connor & Dyce, 2001).…”
Section: Introductionmentioning
confidence: 99%